Ownership type influence on dividend payments in CEE countries - Lace, Natalja; Bistrova, Julija; Kozlovskis, Konstantins (Business: Theory and Practice, 2013)
The present paper provides practical implications for the Central and Eastern European equity investors, who seek dividend income in addition to the capital appreciation. The insight into the dividend puzzle in the CEE companies, provided in the research, gives an overview of the dividend yields and payment stability as well as the relationship between the dividend payments and the type of ownership. Main findings of the study prove that the highest yield and the highest payout ratio are obtained in the case of strategic investor acting as a major shareholder (>10% of ownership capital). Binary logistic regression results provide the possibility to forecast whether the company will pay dividends. The typical dividend payer should not have family/management as a major investor, the ownership still should be concentrated and the investor preferably should be of local origin.